Health behaviors of hospital students at the medical sciences training and research unit in Abidjan - Attoh-Toure, H.; Oussou, Konan R.; Abina, Audrey M. M.; Noufé, S.; Tra, Bi Y. L.; Diallo, M.; Ayeva-Adam, Hayate E.; Konan, Kwakou M.; S. Dagnan, N’Cho (International Journal Of Community Medicine And Public Health, 2024)
Background: The health of medical students is often precarious. Few studies have been carried out on this subject in our country. With the aim of contributing to the improvement of their health, we set out to assess the health behaviours of hospital students at the Training and Research Unit of Medical Sciences in Abidjan. Methods: This descriptive cross-sectional study was conducted among students enrolled in their second year of the Doctor of Medicine program at the Faculty of Medical Sciences in Abidjan. Data collection took place from September 2022 to January 2023 using an online questionnaire distributed through the WhatsApp application. The questionnaire was structured based on the Behavioral Risk Factor Surveillance System (BFRSS 2003) and the Health Promotion Lifestyle Scale. Results: We recorded a total of 384 students, with an average age of 27.2 years, and 85.7% of them were male. Most students (90.6%) reported being in good overall health, while 6.8% mentioned experiencing psychological issues like depression. Good health was more common among male students, those living in university residences, those with health insurance, and those who regularly consumed fruit. In terms of behaviors, unprotected sex was noted in 26% of cases, regular alcohol consumption in 22.4%, and tobacco use in 2.3%. Additionally, 70.8% did not have health insurance. The main health needs expressed were a special medical insurance plan for medical students (97.6%) and access to free vaccinations (2.3%). Conclusions: Students were adopting risky health behaviors. Strategies to promote health in the university environment should be developed and implemented.